The Potential of High Density Scanner Technique for Terrestrial Surface Displacement Studies in Malaysia (2009)
High Density Scanner, as a technology, has gone through an impressive development phase. The development of High Density Scanner (HDS) for the generation of Digital Terrain Model (DTM) has made great progresses in objects measuring, reaching high resolutions and completeness in models reconstruction. Nowadays it is an essential tool that can be used to detect, to better classify and to monitor Terrestrial Surface Displacement (TSD). When studying terrestrial surface displacement, it becomes important to utilize quantitative techniques to develop metric multi temporal 3D models of the TSD and its surroundings. Malaysia is one of the country that facing a lot of TSD event every year especially in the rainy season. Several surveying methodologies are used to investigate the activity of existing TSD: point based (Total Station, GPS) and area based techniques (Photogrammetry and Remote Sensing). The advent of affordable High Density Scanner has opened up a new opportunity in rapid TSD modeling. HDS technology is a surveying method conceived more than ten years ago that in a short time can supply DSM (Digital Surface Model) and good quality DTM as a result of elaborations with specific filtering and interpolation algorithms; only recently has this technique shown growth in development and applications. The objective of this paper is to find the applicability of High Density Scanner (HDS) for Terrestrial Surface Displacement (TSD) studies. A working group consisting of staff from University Technology Malaysia (UTM) International Campus Kuala Lumpur and National Institute of Land and Survey (INSTUN), Behrang, Perak has being setup to carry out this study. The research area is located within the confinement of INSTUN.